Abundant Ce3+ Ions in Au‐CeOx Nanosheets to Enhance CO2 Electroreduction Performance. Issue 17 (2nd April 2019) - Dong, Hao; Zhang, Lei; Li, Lulu; Deng, Wanyu; Hu, Congling; Zhao, Zhi‐Jian; Gong, Jinlong
Abstract: The electroreduction of CO2 to CO provides a potential way to solve the environmental problems caused by excess fossil fuel utilization. Loading transition metals on metal oxides is an efficient strategy for CO2 electroreduction as well as for reducing metal usage. However, it needs a great potential to overcome the energy barrier to increase CO selectivity. This paper describes how 8.7 wt% gold nanoparticles (NPs) loaded on CeO x nanosheets (NSs) with high Ce 3+ concentration effectively decrease the overpotential for CO2 electroreduction. The 3.6 nm gold NPs on CeO x NSs containing 47.3% Ce 3+ achieve CO faradaic efficiency of 90.1% at −0.5 V in 0.1m KHCO3 solution. Furthermore, the CO2 electroreduction activity shows a strong relationship with the fractions of Ce 3+ on Au‐CeO x NSs, which has never been reported. In situ surface‐enhanced infrared absorption spectroscopy shows that Au‐CeO x NSs with high Ce 3+ concentration promote CO2 activation and *COOH formation. Theoretical calculations also indicate that the improved performance is attributed to the enhanced *COOH formation on Au‐CeO x NSs with high Ce 3+ fraction. Abstract : This paper describes how Au‐CeO x nanosheets with high Ce 3+ concentration increase the CO faradaic efficiency for CO2 electroreduction. By Ce 3+ engineering, the CO2 electroreduction activity shows a strong relationship with the fractions of Ce 3+ . Experimental and density functional theory calculations reveal that the enhanced activity originates from high Ce 3+ concentration which facilitates the CO2 adsorption and the formation of *COOH.